2015
DOI: 10.2174/156800961506150805153230
|View full text |Cite
|
Sign up to set email alerts
|

A New Strategy to Target Acute Myeloid Leukemia Stem and Progenitor Cells Using Chidamide, a Histone Deacetylase Inhibitor

Abstract: Leukemia stem cells (LSCs) are responsible for treatment failure and relapse in acute myeloid leukemia (AML). Therefore, development of novel LSCs-targeting therapeutic strategies is of crucial clinical importance to improve the treatment outcomes of AML. Histone deacetylase (HDAC) inhibitors have shown potent and specific anticancer stem cell activities in preclinical studies. Chidamide, a novel benzamide-type selectively HDAC inhibitor, has been reported to induce G1 arrest and apoptosis in the relatively ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 0 publications
1
34
0
Order By: Relevance
“…A possible mechanism may be the downregulation of JAK2/STAT3 signalling through SOCS3 upregulation. 33 Li et al 34 also observed that chidamide specifically induced apoptosis in LSC-like cells and primary AML CD34 + cells in a concentration-and time-dependent manner by activation of reactive oxygen species.…”
Section: F I G U R E 1 (A) Bone Marrow Aspirate Showing Monoblasts (Wmentioning
confidence: 96%
“…A possible mechanism may be the downregulation of JAK2/STAT3 signalling through SOCS3 upregulation. 33 Li et al 34 also observed that chidamide specifically induced apoptosis in LSC-like cells and primary AML CD34 + cells in a concentration-and time-dependent manner by activation of reactive oxygen species.…”
Section: F I G U R E 1 (A) Bone Marrow Aspirate Showing Monoblasts (Wmentioning
confidence: 96%
“…The effect of the inhibitor on the resistance of Cal-27 CisR cell line to Cisplatin was assessed by cell viability assay. The cells were treated with the IC50 concentration of Cisplatin (20 mM) in combination with NCT-501 at varied concentration (10,20,40, and 80 nM). Cytotoxicity assays showed a 16% decrease in cell viability (56 AE 1.7% vs. 40 AE 6.4%) in the Cal-27 CisR cell line at 20nM concentration of the inhibitor, though the difference was not statistically significant ( Figure 7E).…”
Section: Nct-501 (Aldh1a1 Inhibitor) Inhibited Functional Properties mentioning
confidence: 99%
“…Thus, this has become a major hindrance to success of AML treatment. 5 To prolong the duration of DFS as well as overall survival, new therapeutic agents targeting LSCs with low/non systemic toxicity are urgently needed for AML treatment.…”
mentioning
confidence: 99%